An ethnography on the Maizbhandar: locating within cultural, religious and political dimensions - Awal, Arefin Noman Bin (BRAC University, 2017)
This thesis is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Social Science in Anthropology, 2016.